FEATURES OF TRIZ TECHNOLOGY APPLICATION WITH A COMPETENCE APPROACH IN TEACHING ELEMENTARY SCHOOL STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article presents the means of forming competencies in junior schoolchildren, highlights the techniques and methods of TRIZ technology used in the classroom in primary grades.